Analisis Hukum Terhadap Penanggulangan Tindak Pidana Perambahan Kawasan Hutan (Studi Putusan Nomor 3684/Pid.Sus/2015/PN-Mdn) - Sianturi, Senior; Mulyadi, Mahmud; Eddy, Triono (Universitas Medan Area, 2020)
This article discusses the study of the Legal Analysis of the Criminal Act of Exploiting Forest Areas in this case the analysis of judges' considerations of Decision Number 3684/Pid.Sus/2015/PN-Mdn and to examine the judicial barriers of judges in dropping Decision Number 3684/Pid.Sus/2015/PN-Mdn. This study uses a normative juridical approach and is presented in the form of analytical descriptive. The results found were criminal legal arrangements regarding forestry crimes regulated in Act Number 18 of 2013 concerning Prevention and Eradication of Forest Destruction. Judge consideration analysis of the decision No. 3684/Pid.Sus/2015/PN-Mdn) which states the defendant Aswin Syahfitri a.k.a. Aswin has been proven legally and convincingly guilty of committing a criminal offense Individuals who deliberately carry out plantation activities without the permission of the Minister. Internal juridical barriers in imposing a criminal act for encroachment of forest areas in the Medan District Court is that there are no internal obstacles. The Panel of Judges in considering forestry criminal cases needs to impose a criminal which also refers not only to the forestry law, but also needs to include the criminal in the environmental law and also the plantation law.Â